PENDAMPINGAN UMKM POSBINDU DAHLIA INDAH PETUAKAN SELATAN MELALUI PEMASARAN DIGITAL DAN PENGUATAN MANAJEMEN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN DAYA SAING USAHA - Anindya Putri Pradiptha; Deden Kurniawan; Mia Laksmiawati; Muhammad Iqbal Naufal (CV. Denasya Smart Publisher, 2025)
The mentoring program for Posbindu Dahlia Indah Petuakan Selatan MSMEs aimed to enhance business competitiveness through digital marketing strategies and human resource management strengthening. The challenges faced by this MSME included suboptimal use of digital platforms, unattractive packaging, and ineffective human resource management. The community engagement activity was conducted over three months using a participatory approach involving direct training, consultations, and periodic evaluations. The results showed significant improvements in the activation and optimization of e-commerce accounts, packaging quality enhancement, and a more structured division of tasks. Increased HR competencies contributed to higher production capacity and operational efficiency. This activity concluded that the synergy between digital marketing and HR management strengthening successfully improved product visibility and the competitiveness of MSMEs in the digital marketplace.